Meet the Expert : Selected Experts on AI in Banking and Finance - Alexander, Brigitte; Sharma, Abhi; Kumar, Vinay (O'Reilly Media, Incorporated, 2020)
Sponsored by Intel Join us for a new Meet the Expert series from Intel. Each event will feature three short back-to-back presentations from Intel partners from industries including healthcare, banking and finance, retail, security, and more. Learn how companies are solving real-world business problems across a variety of AI workloads and how enterprise customers are using these solutions today.